2013
DOI: 10.1038/nature12493
|View full text |Cite
|
Sign up to set email alerts
|

A quantum access network

Abstract: The theoretically proven security of quantum key distribution (QKD) could revolutionise how information exchange is protected in the future [1,2]. Several field tests of QKD have proven it to be a reliable technology for cryptographic key exchange and have demonstrated nodal networks of point-to-point links [3][4][5]. However, so far no convincing answer has been given to the question of how to extend the scope of QKD beyond niche applications in dedicated high security networks. Here we show that adopting sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
223
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(223 citation statements)
references
References 30 publications
0
223
0
Order By: Relevance
“…1(a), two light pulses are independently encoded and sent by Alice and Bob to a central node, Charlie. This is similar to a quantum access network configuration [20], but in MDI-QKD the central node does not need to be trusted and could even attempt to steal information from Alice and Bob. To follow the MDI-QKD protocol, Charlie must let the two light pulses interfere at the beam splitter inside his station and then measure them.…”
mentioning
confidence: 99%
“…1(a), two light pulses are independently encoded and sent by Alice and Bob to a central node, Charlie. This is similar to a quantum access network configuration [20], but in MDI-QKD the central node does not need to be trusted and could even attempt to steal information from Alice and Bob. To follow the MDI-QKD protocol, Charlie must let the two light pulses interfere at the beam splitter inside his station and then measure them.…”
mentioning
confidence: 99%
“…Based on the passive beam splitter, Townsend et al presented and realized the first QKD network [17,18]. And since then, researchers have devised and developed an impressive collection of network architectures for QKD [19][20][21][22][23][24][25][26][27][28][29][30][31]. Combined with increasingly mature QKD devices, these developments enabled QKD networks to be deployed over real-world telecommunication networks.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum key distribution 1,2 systems based on weak-coherent optical pulses have been reported that allow unique cryptographic keys to be shared between directly connected users on point-to-point [3][4][5] or point-to-multipoint links 6 . To establish fully quantum multipartite networks, that avoid trusting intermediate parties, 7 it is necessary to route quantum signals through a backbone of quantum nodes.…”
Section: Introductionmentioning
confidence: 99%